Design and characterisation of vitrimer-like elastomeric composites from HXNBR rubber. Issue 37 (7th August 2020) - Kaiser, Simon; Jandl, Julius; Novak, Patrick; Schlögl, Sandra
Abstract : Vitrimer-like elastomer composites are prepared using epoxy-functionalized filler as crosslinker and their good mechanical properties and stress relaxation is demonstrated. Abstract : The present study aims at the incorporation of vitrimer-like properties into elastomeric composites as a promising approach towards the sustainable production of rubber-based materials. In particular, hydrogenated carboxylated nitrile butadiene rubber (HXNBR), as a technically relevant high-performance rubber, is covalently cross-linked with epoxy group-functionalised calcium silicate (Esilicate) across its pending carboxylic acid moieties. Reaction with the reactive functions attached on the filler surface results in the formation of β-hydroxyl ester linkages at the HXNBR–Esilicate interface, which undergo thermo-activated transesterifications in the presence of a suitable catalyst. Topology rearrangements in the composites are confirmed by stress relaxation measurements at elevated temperatures. Comparison with an unfilled reference network reveals that the extent of stress relaxation can be mostly maintained upon the addition of the reactive filler even at large quantities. The Esilicate serves as both cross-linker and reinforcing filler, leading to a significant enhancement of the mechanical properties.